2002
DOI: 10.1111/j.1574-6941.2002.tb01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic characterization of the bacterial assemblage associated with mucous secretions of the hydrothermal vent polychaete Paralvinella palmiformis

Abstract: As part of an ongoing examination of microbial diversity associated with hydrothermal vent polychaetes of the family Alvinellidae, we undertook a culture-independent molecular analysis of the bacterial assemblage associated with mucous secretions of the Northeastern Pacific vent polychaete Paralvinella palmiformis. Using a molecular 16S rDNA-based phylogenetic approach, clone libraries were constructed from two samples collected from active sulfide edifices in two hydrothermal vent fields. In both cases, clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 64 publications
(103 reference statements)
2
62
0
Order By: Relevance
“…One group of Verrucomicrobia clones were 100% similar to clones from Svalbard sediments (Table 4). The remaining Verrucomicrobia clones were ≥92% similar to other clones from marine sediments (Alain et al ., 2002; Inagaki et al ., 2006). The Verrucomicrobia are widely distributed in the environment (Hedlund et al ., 1996), and numerous reports have identified Verrucomicrobia relatives in marine sediments (Alain et al ., 2002; Teske et al ., 2002; Mills et al ., 2004; Inagaki et al ., 2006).…”
Section: Discussionmentioning
confidence: 54%
“…One group of Verrucomicrobia clones were 100% similar to clones from Svalbard sediments (Table 4). The remaining Verrucomicrobia clones were ≥92% similar to other clones from marine sediments (Alain et al ., 2002; Inagaki et al ., 2006). The Verrucomicrobia are widely distributed in the environment (Hedlund et al ., 1996), and numerous reports have identified Verrucomicrobia relatives in marine sediments (Alain et al ., 2002; Teske et al ., 2002; Mills et al ., 2004; Inagaki et al ., 2006).…”
Section: Discussionmentioning
confidence: 54%
“…AJ877255) and strain Ko711 from Kolbeinsey Ridge, Iceland (99.5 % similarity, GenBank accession no. AF550592), and to six deep-sea environmental sequences (Alain et al, 2002(Alain et al, , 2004Goffredi et al, 2005) obtained from clone libraries (Fig. 1).…”
Section: Strain Haw-eb21mentioning
confidence: 99%
“…Also, the representatives of this group are considered to be an important part of marine-animal microbial populations, as indicated by data from culture-independent molecular analyses (Cooney et al, 2002;Ló pez-García et al, 2002;Webster et al, 2004). For example, Alain et al (2002) examined the microbial assemblage associated with the hydrothermal vent polychaete Paralvinella palmiformis of the north-eastern Pacific by using 16S rRNA gene sequencebased phylogenetic analysis; they reported that members of the Cytophaga-Flavobacterium group were identified frequently in 16S rRNA gene clone libraries.…”
mentioning
confidence: 99%